An investigation of mechanical and wear properties of AA6061 reinforced with silicon carbide and graphene nano particles-Particulate composites. (2016) - Radha, A.; Vijayakumar, K.R.
Abstract: Nowadays, Aluminium Matrix Composites (AMCs) find application in various fields like Automobiles, Aeronautical etc., due to its light weight and high strength. Also, nano particles are used as reinforcement in AMCs due to the fact that it can serve as a very good reinforcing agent and adds more stiffness. Aluminium Alloy (AA) is mixed with nano particles like graphene as reinforcement to prepare AMCs. Reinforcement of graphene with the matrix metal leads to enhancement in mechanical properties without any considerable increase in weight of the material. In this study, samples of AA6061 reinforced with constant wt% of Silicon Carbide (SiCp ) (10% of AA) and varying wt% of graphene (0%, 0.3%, 0.5%, and 0.7%) were fabricated by Stir Casting technique. The specimens were undergone through various tests like tensile, flexural, hardness, impact and wear and Microstructure analysis. The optical and SEM images shows that uniformly distributed in AMCs.The overall test results are revealed that the addition of graphene helped to improve the mechanical properties significantly when compared to reinforced Aluminium with SiCp.